Mikhail Efimovich Budarin — scientist and enlightener. From history of culture in Siberian Territory (1940’s–2000’s) - S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
Socialist construction carried out in the USSR is a separate topic based on knowledge of the history of the social and economic development of the country of study. One of the researchers and popularizers of socialist construction was M. E. Budarin. As a journalist, he conveyed to his contemporaries information about the transformations taking place in the Ob North, as a writer he created pictures of the life and life of the peoples of Siberia in various periods of their history. Appeal to scientific activity has become a step in understanding the history of the development of the region studying the activities of authorities in its development, analysis of the impact of development on the peoples of the region. The teaching work expanded the possibilities of popularizing the history of the entry of Siberia into Russia and the transformation of the region in the Soviet period. Over the years of activity, the multifaceted personality of M. E. Budarin was revealed, who embodied in his work all the difficulties of Soviet history